1984
DOI: 10.1093/cvr/18.5.270
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac compliance and dimensions in carbon monoxide-induced cardiomegaly

Abstract: Adult male rats inhaled 500 ppm CO continuously for 38 to 47 days to produce significant cardiomegaly. In a first experiment in which heart wall stiffness was examined, haematocrit rose 45.1% and the ratio of the sum of right ventricle (RV) and left ventricle (LV) to body weight (mg X g-1) increased from 2.69 to 3.34. Compliance (ml X mmHg-1) of CO LV's and RV's studied from 0 to 25 mmHg intraluminal pressure, was generally greater than that of LV's and RV's from controls at the same pressure. These difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Several studies have revealed detrimental effects of HO-derived by-products. For example, chronic CO inhalation at a dose mimicking levels normally registered with tobacco smoking (500 parts per million) worsens post-MI LV remodeling (37,42). In addition, CO inhibits oxygen binding to myoglobin (19), and CO inhibits other hemoproteins, including cytochrome c (43,45,46) and endothelial nitric oxide synthase.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed detrimental effects of HO-derived by-products. For example, chronic CO inhalation at a dose mimicking levels normally registered with tobacco smoking (500 parts per million) worsens post-MI LV remodeling (37,42). In addition, CO inhibits oxygen binding to myoglobin (19), and CO inhibits other hemoproteins, including cytochrome c (43,45,46) and endothelial nitric oxide synthase.…”
Section: Discussionmentioning
confidence: 99%
“…1 mg. A relative mass determination of each region was carried out using multiple exponential regression equations, relating heart weight and body weight of normal rats obtained previously. l 2 The stored NMR imaging data were analyzed on a cathode ray screen using Siemens software for distance measurements. The slices were coded so that the individual (Bambach) making the measurements was unaware of the previous treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, we demonstrated that under exposure to several concentrations of CO, hypertrophy begins to occur, but, at 530 ppm CO exposure, hypertrophy is significant after 1-wk exposure and is maintained throughout CO exposure to a similar value (25%). Moreover, CO exposure led to hypertrophy by volume overload (21). Cardiomegaly developed in both ventricles and atria with the addition of new myocardial constituents (19) and involved an increase in lumen dimensions with some primarily small increase in wall thickness of the ventricles (i.e., eccentric hypertrophy) (21).…”
Section: Does This Increase In 4-ap-sensitive Currents Have Functionamentioning
confidence: 99%
“…Moreover, CO exposure led to hypertrophy by volume overload (21). Cardiomegaly developed in both ventricles and atria with the addition of new myocardial constituents (19) and involved an increase in lumen dimensions with some primarily small increase in wall thickness of the ventricles (i.e., eccentric hypertrophy) (21).…”
Section: Does This Increase In 4-ap-sensitive Currents Have Functionamentioning
confidence: 99%